Comparative studies of value orientations: potential, limitations, and the logic of development - I V Trotsuk; E A Savelieva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
The article presents an attempt to identify the current status of the comparative (or cross-cultural) studies in the sociological tradition by indicating basic contexts of discussing relevant issues in the sociological discourse. First, there is a quite ambiguous categorical apparatus of the comparative analysis even at the level of the key nominations of the subject of cross-cultural studies (the ratio of in-country and cross-country comparisons, of regional, socio-cultural, socio-economic and other aspects in the structure and size of the population, samples and sub-samples, survey techniques, etc.). Second, the history of comparative studies is highly fragmented due to the lack of a coherent tradition and a variety of bright methodological principles and techniques, which experienced modifications at the stages of collection and analysis of empirical data (especially due to the need to take into account differences in the subsamples’ worldviews and to avoid systematic biases that generate differences in data instead of measuring the existing ones). Third, there is a variety of attempts to structure the field of comparative studies on various grounds, which often leads to the opposite result - even more confusion in nominations. Finally, there are recognized since the formation of the comparative research orientation in sociology but still unresolved (partly non-resolvable in principle) problems of ensuring the equivalence of data, primarily with the standardized conceptualization and operationalization of the basic concepts of the project and use of a single method of sampling, data collection and analysis.